Nursing-LED and Nursing Supported Interventions to Enhance Resilience Among Vulnerable Populations in Post-Disaster Settings: A Scoping Review - Putri, Aliza Zulpa; Afriyani, Firda; Pujowati, Pujowati; Fazriyyah, Yuni Fuji; Sari, Puput Antika; Sujana, Wendi; Jalaludin, Andi Mohamad; Saputri, Baiq Dara Wulandari; Supriyansah, Gumilar; Meyzabellah, Meriem; Nurdin, Irpan Muhamad; Wardaya, Wildan Akhmad Ihza; Kosasih, Cecep Eli; Trisyani, Yanny; Minh, Vo Hoang (Jurnal Pendidikan Keperawatan Indonesia, 2026)
Introduction:  Increasing global disasters due to climate change have caused severe health crises, especially for vulnerable groups like older adults, people with disabilities, and those with chronic diseases. This study was conducted to map nursing interventions designed to enhance the resilience of vulnerable populations. Methods:  This study used scoping review following Arksey and O’Malley and PRISMA-ScR guidelines. The eligibility were structured using the PCC (Population, Concept, Context) framework. A systematic search was executed for original English articles that published between 2016-2026 and written in english from databases including PubMed, Scopus, and EBSCOhost. Study selection was performed independently by two reviewer, and data extraction utilized a standardized charting form. Methodological quality was evaluated using the Joanna Briggs Institute (JBI) Critical Appraisal Checklists. Results:  A total of 275 articles were identified from three databases through the literature search. After screening, 15 final articles were included in the current review. The synthesis categorized interventions into two primary domains: (1) Physical Domain, comprising chronic disease management and self-management support, household emergency preparedness, and community healthcare outreach to navigate disaster-affected terrain; and (2) Psychological Domain, encompassing community-based psychosocial and trauma skills programs (e.g., SOLAR, CBDMHI), digital-based psychosocial interventions, and self-efficacy-focused education. Findings indicate that nurses function as critical care coordinators and community mobilizers. However, the synthesis reveals significant evidence gaps regarding the long-term sustainability of these interventions, the limited representation of populations with "layered vulnerabilities," and the need for standardized resilience metrics. Conclusion: Nursing-led interventions are paramount for sustainable resilience by integrating physical domain support with psychosocial and digital-based care. These strategies effectively leverage nursing roles as coordinators and community mobilizers, though future efforts must prioritize longitudinal implementation and policy integration to ensure long-term recovery for vulnerable populations